Development of a marital self-disclosure programme for alleviating the fear of cancer recurrence in patients with gastric cancer and undergoing chemotherapy: a modified Delphi method - Zhou, Ye; Che, Chong Chin; Chong, Mei Chan; Zhao, Haiyan (Frontiers in Psychology, 2024)
Aim: This study aimed to develop a marital self-disclosure programme to alleviate the fear of cancer recurrence in patients with gastric cancer who are undergoing chemotherapy.Methods: Data from available literature and stakeholder interviews were utilized to formulate the initial draft of a marital self-disclosure programme aimed to alleviate the fear of cancer recurring in patients with gastric cancer and undergoing chemotherapy. A panel of experts subsequently conducted a two-round modified Delphi method to finalize the programme.Results: A total of 13 experts participated in the first round of consultation, while 11 experts were involved in the second round, as two experts withdrew due to unavailability. The response rates of both rounds of expert consultation were 100% and 84.62%, respectively, and the expert authority coefficients (Cr) of the programme were 0.83 and 0.84, respectively. The coordination coefficients of the expert opinions were 0.124 (  ²=61.214, P=0.010) and 0.167 (  ²=69.668, P=0.001) for each Delphi round. The average score of the second round was (4.545±0.688) to (5.000 ± 0) , with a full score ratio of 0.55-1.00. The coefficient of variation (CV) ranged from 0 to 0.031. Outcomes from both rounds of consultations were considered acceptable and credible. The finalized marital self-disclosure programme for alleviating the fear of cancer recurrence in patients with gastric cancer undergoing chemotherapy consists of two parts; disclosure guidance for patients and their spouse with nine items, and the structure and themes of marital self-disclosure with 31 items.Patient or Public Contribution: After two rounds of expert consultations, the marital self-disclosure programme for patients with gastric cancer undergoing chemotherapy is suggested to be scientifically valid and reliable. This programme is anticipated to potentially support patients and their spouses effectively by providing a reliable intervention plan focused on alleviating the fear of cancer recurrence.